Preservation of oil slick samples on adsorbent Teflon fabric: Potential for deployment aboard autonomous surface vessels. (August 2021) - Wang, David T.; Meurer, William P.; Nguyen, Thao N.; Shipman, Gregory W.; Koenig, David
Abstract: In this communication, we report results of an experiment in which crude oil adsorbed on Teflon fabric is exposed to conditions expected in natural ocean-surface collection vehicle containers over a period of 3 months. Samples were recovered at designated time points and analyzed to determine degree of preservation of molecular signatures. Ratios of saturate hydrocarbons were preferentially preserved compared to those of aromatic compounds. Unsubstituted aromatic compounds such as naphthalene and dibenzothiophene were removed at higher rates relative to methyl-substituted homologues owing to differences in biodegradability and solubility. Ratios of important marker compounds persist over several months with sufficient fidelity for accurate determination of source-rock facies and thermal maturity. Collection and storage of oil samples on small pieces of adsorbent Teflon mesh broadens the opportunity space for collection of organic geochemistry data. Deployment of automated samplers equipped with such Teflon meshes aboard autonomous surface vehicles and human-operated vessels promises cheaper, better coverage of geochemical data in seep, slick, and spill surveys conducted for research, exploration, monitoring, and emergency response efforts. Highlights: Oil adsorbed on Teflon mesh preserves diagnostic geochemical markers for 3 months. Saturate biomarker ratios are better preserved than aromatic hydrocarbon ratios. No additional preservatives are necessary as long as exposure to air is limited. Autonomous survey vessels can collect oil slick samples using Teflon mesh samplers.